Observation of CH⋅⋅⋅π Interactions between Methyl and Carbonyl Groups in Proteins. Issue 26 (22nd May 2017) - Perras, Frédéric A.; Marion, Dominique; Boisbouvier, Jérôme; Bryce, David L.; Plevin, Michael J.
Abstract: Protein structure and function is dependent on myriad noncovalent interactions. Direct detection and characterization of these weak interactions in large biomolecules, such as proteins, is experimentally challenging. Herein, we report the first observation and measurement of long‐range "through‐space" scalar couplings between methyl and backbone carbonyl groups in proteins. These J couplings are indicative of the presence of noncovalent C−H⋅⋅⋅π hydrogen‐bond‐like interactions involving the amide π network. Experimentally detected scalar couplings were corroborated by a natural bond orbital analysis, which revealed the orbital nature of the interaction and the origins of the through‐space J couplings. The experimental observation of this type of CH⋅⋅⋅π interaction adds a new dimension to the study of protein structure, function, and dynamics by NMR spectroscopy. Abstract : Don't neglect the little ones : Solution NMR spectroscopy and DFT calculations showed the existence of weak, hydrogen‐bond‐like C−H⋅⋅⋅π interactions in proteins between methyl donor groups and peptide‐bond acceptor groups (see picture). As large numbers of C−H⋅⋅⋅πCO interactions are present in proteins, they presumably make an important cumulative contribution to protein structure, dynamics, and function.